Anatomical studies on drought-stressed wheat plants (Triticum aestivum L.) treated with some bacterial strains - El-Afry, Mohamed Mabrouk (Acta Biologica Szegediensis, 2012)
Pot experiments were carried out during successive winter season of 2010/2011 in the greenhouse conditions at the Department of Agricultural Botany, Faculty of Agriculture, Kafrelsheikh University. The aim of this study was designed to investigate the effect of two treatments of bacterial endophytes strains Azotobacter chrocoocum (E1) and Pseudomonas fluorescens. (E2) individually whether as grains soaking and foliar application on anatomical features of two wheat plants (Triticum aestivum L.) cultivars (Sakha 93 and Gmiza 9) grown under three levels of irrigation water deficit stress (drought) 75, 50 and 25% field capacity (FC). Wheat stem and flag leaf anatomical parameters were take into account were vascular bundle dimensions, xylem vessel diameters as well as epidermis tissue thickness. Moreover, mesophyll tissue thickness values in flag leaf were calculated. The obtained results that, irrigation water deficit levels (75, 50 and 25% FC) treatments decreased revealed the values of the anatomical parameters such as thickness of epidermis, ground, mesophyll and phloem tissues, diameter of xylem vessel, and dimensions of vascular bundles of the tested wheat cultivars. While, treating wheat plants with Azotobacter chrocoocum (E1) and Pseudomonas sp. (E2) significantly increased the values of the tested anatomical characters. This study suggests that the effects of the tested bacterial endophytes treatments act as protective factors against irrigation water deficit and can improve water bio-productivity.